A Dose‐Confirmation Phase 1 Study to Evaluate the Safety and Pharmacology of Glucarpidase in Healthy Volunteers. Issue 3 (25th August 2021) - Fukaya, Yutaka; Kimura, Toshimi; Yoshimura, Kenichi; Umemura, Kazuo; Kawamoto, Hiroshi
Abstract: Glucarpidase rapidly decomposes methotrexate. A phase 1 study of glucarpidase in an open‐label, randomized parallel group was conducted to evaluate the safety, pharmacokinetics, and other pharmacologic effects in Japanese healthy volunteers without methotrexate treatment. A dose of 50 U/kg (n = 8) or 20 U/kg (n = 8) of glucarpidase was administered as an intravenous injection, with 1 repeated dose at 48 hours after the first dose. No dose‐limiting toxicities, no significant clinical examination findings, and no clinically relevant differences between dose levels were observed. The pharmacokinetic parameters at a first dose of 20 or 50 U/kg were similar to those at a second dose and were as follows: half‐life, 7.45 and 7.25 hours; area under the plasma concentration–time curve from time 0 to infinity, 8.25 and 19.05 μg·h/mL; total clearance, 4.85 and 5.47 mL/min; and volume of distribution during the elimination phase, 3.12 and 3.41 L, respectively. The area under the plasma concentration–time curve increased in a generally linear dose‐proportional manner. An ethnicity specificity in the pharmacokinetic profile was not observed in Japanese volunteers. The serum folate concentration decreased after glucarpidase administration in all the volunteers. The production of anti‐glucarpidase antibody was observed in many cases in both cohorts. Although the long‐term effect of anti‐glucarpidase antibody will need to be investigated in the future, the effects produced by the anti‐glucarpidase antibody were not influenced by the pharmacokinetics of glucarpidase within 96 hours after the first dose. The observed safety and tolerability, pharmacokinetics, and pharmacodynamics support the continued evaluation of glucarpidase in the patients with lethal methotrexate toxicities.